HUBUNGAN PENINGKATAN PENGETAHUAN DAN SIKAP IBU DALAM MENGATASI KEJADIAN DIARE PADA BALITA: RELATIONSHIP BETWEEN INCREASED KNOWLEDGE AND MOTHER'S ATTITUDE IN OVERCOMING DIARRHEA IN TODDLERS - Dian Anggri Yanti; Batubara, Khairunnisa; Harahap, Rahmat Ali Putra (Intan Husada : Jurnal Ilmiah Keperawatan, 2025)
Introduction: Diarrhea is one of the diseases that can cause death in toddlers. Toddler diarrhea occurs due to infections caused by viruses and bacteria entering the body through the digestive tract. Diarrhea causes toddlers to experience dehydration, hypoglycemia, hypokalemia, and malnutrition. Several changes occur in toddlers during diarrhea, including becoming unenthusiastic, weak, and fussy. It is often accompanied by vomiting and dehydration due to lack of fluids. The purpose of this study was to improve mothers' knowledge and attitudes in dealing with diarrhea. This can be done through socialization and health education activities so that mothers' knowledge increases and they have a better attitude in maintaining a healthy lifestyle for toddlers. Method: This study applies an analytical observational research type using a cross-sectional research design so that a picture of a phenomenon can be obtained. The sample was mothers who had toddlers in Lubuk Pakam Village who were determined using the purposive sampling method so that the number of samples obtained was 25 respondents. The instruments used were a questionnaire on the level of knowledge and a Likert scale for attitudes. The data obtained will be analyzed for the distribution of respondents, distribution of the level of knowledge, and attitudes. Then the data will be connected to examine the relationship between knowledge and attitudes in dealing with diarrhea incidents using the chi-square test. Results: The results of the analysis show that many respondents are in the age categories of 20-25 years and 26-31 years, with a high school education background, and work as housewives. Most respondents have a high level of knowledge and have a good attitude in dealing with diarrhea incidents. The conclusion is that the knowledge and attitude of mothers have a close relationship in dealing with diarrhea incidents with a significance value of 0.0018.